A Morphological and Topographical Study of Diaphyseal Nutrient Foramen (NF) In Dried Human Adult Long Bones of Upper Limbs : Nutrient Foramen in Upper Limbs - William, Godfrey Paul; Munawar, Saira; Sohail, Shumaila; Salauddin, Mehreen; Fahim, Nimrah; Nawaz, Arooj; Sayal, Shaukat (Pakistan Journal of Health Sciences, 2025)
The morphological and topographical characteristics of diaphyseal Nutrient Foramina (NF) in the long bones of the upper limbs is essential for optimizing surgical interventions, particularly in fracture management and bone grafting procedures. Objective: To assess the anatomical features (number, location and foramina index) of diaphyseal NF in cadaveric long bones of upper limb in adult Pakistani population. Methods: This cross-sectional study was undertaken on human cadaveric upper limb bones from the bone bank of the Anatomy department of FMH College of Medicine and Dentistry, Lahore. The age and gender of the bones were not known, and the duration of the study was four months. A total of 195 non-pathological, undistorted bones of upper limb (57 clavicles, 34 humeri, 50 radii and 54 ulnae) with were randomly selected. Results: In cases of clavicle 58% had a single NF (NF), 33% double & 5% triple, in humerus 100% had a single NF, 96% of radii had a single NF & 4% double whereas in ulna 98% had single NF and 2% double. In majority of the clavicle, humerii and radii the NF was in the 2/3rd of the bone whereas in case of ulnae majority of NF occupied the proximal 1/3rd of the shaft of the ulnae. Conclusion: A good knowledge about the anatomy of the NF is necessary for orthopaedic or trauma surgeons while doing critical bone reconstructive or graft implantation surgeries.